1997
DOI: 10.1136/gut.40.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of primed infusions with high dose ranitidine and omeprazole to maintain high intragastric pH in patients with peptic ulcer bleeding: a prospective randomised controlled study.

Abstract: Background-In healthy subjects, continuous infusions of high dose ranitidine and omeprazole produce high intragastric pH values. Aim-To test the hypothesis that both drugs also maintain high intragastric pH values in patients with bleeding ulcers. Patients and Methods-In two parallel studies, 20 patients with bleeding duodenal ulcers and 20 patients with bleeding gastric ulcers were randomly assigned to receive either ranitidine (0.25 mg/kg/hour after a bolus of 50 mg) or omeprazole (8 mg/hour after a bolus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 42 publications
2
112
0
6
Order By: Relevance
“…Studies in white subjects have demonstrated that a high dose of omeprazole, like the one we used, can neutralize intragastric pH. [4][5][6] The parietal-cell mass in Asian subjects is smaller than that in white subjects. 24 We therefore did not consider pH monitoring necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in white subjects have demonstrated that a high dose of omeprazole, like the one we used, can neutralize intragastric pH. [4][5][6] The parietal-cell mass in Asian subjects is smaller than that in white subjects. 24 We therefore did not consider pH monitoring necessary.…”
Section: Discussionmentioning
confidence: 99%
“…2 In a multicenter trial that compared famotidine infusion with placebo infusion in 1005 patients, the rate of recurrent bleeding was similar in the two groups. 3 In vivo studies have shown that a regimen that includes high doses of a proton-pump inhibitor maintains intragastric pH at a nearly neutral level 4,5 and inhibits acid production more effectively than does an infusion of H 2 -receptor antagonists. Furthermore, tolerance of the antisecretory effect of H 2 -receptor antagonists, with loss of pH control, develops during the 72-hour period of infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the effect of these drugs is limited to keeping intragastric pH above 4 during 6 of the 24 hours in a day, they provide disappointing results in terms of esophageal healing rate and even symptom relief (4,5) . Association of prokinetic agents to H2 receptor antagonists for the treatment of GERD has also failed to significantly improve therapeutic effectiveness, especially in more severe grades of reflux esophagitis (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the intragastric pH (G -pH) must be raised. For hemostasis when intragastric bleeding occurs, the G -pH must be raised above 6 7) . Gastric mucosal bleeding drops markedly at G -pH >6.4 8) .…”
Section: Introductionmentioning
confidence: 99%